2020
DOI: 10.3390/buildings10030040
|View full text |Cite
|
Sign up to set email alerts
|

Urban Morphology and Outdoor Microclimate around the “Shophouse” Dwellings in Ho Chi Minh City, Vietnam

Abstract: The underestimation of population growth has resulted in the disruptive and uncontrolled expansion of settlements in Ho Chi Minh City (HCMC). The outcome is a complicated mix of new spontaneous dwelling areas featuring a number of distinct urban morphologies. Previous studies have shown the impacts of urban morphologies on comfort levels in outdoor environments. The paper examines the correlation of microclimatic conditions and constituents that create the urban spatial form of residential neighbourhoods, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Therefore, these findings may be cautiously applicable to similar spatial settings in SEA cities with comparable climatic conditions, particularly regarding the beneficial daytime impacts of tree shade. However, a more universal transferability of findings to other climatic settings, and urban morphologies different from wide, shallow street canyons, is limited: in a comparison of air temperature in Ho Chi Minh City across urban morphologies, differences of up to 2 K were found between spatial settings [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these findings may be cautiously applicable to similar spatial settings in SEA cities with comparable climatic conditions, particularly regarding the beneficial daytime impacts of tree shade. However, a more universal transferability of findings to other climatic settings, and urban morphologies different from wide, shallow street canyons, is limited: in a comparison of air temperature in Ho Chi Minh City across urban morphologies, differences of up to 2 K were found between spatial settings [33].…”
Section: Discussionmentioning
confidence: 99%
“…For a business district quarter in Ho Chi Minh City, an assessment of the (combined) impacts of building orientation, surface materials, and greening on air temperature and OTC concluded that street greenery, i.e., a maximization of street tree plantings, is associated with the most noticeable cooling impact and improvement of OTC, derived from physiological equivalent temperature (PET) [32]. Furthermore, also focusing on Ho Chi Minh City, thermal comfort around so-called "shophouse" dwellings has been assessed to compare air temperature across different urban morphologies [33], and in the city of Ha Tinh, PET was modeled for a residential block, concluding that in comparison to larger areas of grassy vegetation, tree canopies are more suitable for the improvement of OTC, and that waterbodies effectively cool air, but lead to a potential deterioration of OTC [34].…”
Section: Of 26mentioning
confidence: 99%
“…Downes et al (2016) showed that shophouse archetypes, also often referred to as row-or tube-houses in the literature, and commonly termed nhà ống in Vietnamese, are the predominant residential structures in HCMC, making up over 95% of the building stock in 2010 [44]. Inspired by the local vermicular architectural customs and policies that incentivized households to pay property tax based on the width of the first floor, rather than the total area, shophouse archetypes are usually located in a rectangular plot which is much longer than it is wide, typically ranging from 3 to 5 m in breadth and 12-20 m in length [74][75][76][77]. With the narrow side, fronting a street or alleyway, the term "shophouse" originated as whole or part of the building's ground floor is typically reserved for retail or office space.…”
Section: Introductionmentioning
confidence: 99%